Extinction during reconsolidation eliminates recovery of fear conditioned to fear-irrelevant and fear-relevant stimuli - Thompson, A.; Lipp, Ottmar (Elsevier, 2017)
© 2017 Elsevier LtdExtant literature suggests that extinction training delivered during the memory reconsolidation period is superior to traditional extinction training in the reduction of fear recovery, as it targets the original fear memory trace. At present it is debated whether different types of fear memories are differentially sensitive to behavioral manipulations of reconsolidation. Here, we examined post-reconsolidation recovery of fear as a function of conditioned stimulus (CS) fear-relevance, using the unconditioned stimulus (US) to reactivate and destabilize conditioned fear memories. Participants (N = 56; 25 male; M = 24.39 years, SD = 7.71) in the US-reactivation and control group underwent differential fear conditioning to fear-relevant (spiders/snakes) and fear-irrelevant (geometric shapes) CSs on Day 1. On Day 2, participants received either reminded (US-reactivation) or non-reminded extinction training. Tests of fear recovery, conducted 24 h later, revealed recovery of differential electrodermal responding to both classes of CSs in the control group, but not in the US-reactivation group. These findings indicate that the US reactivation-extinction procedure eliminated recovery of extinguished responding not only to fear-irrelevant, but also to fear-relevant CSs. Contrasting previous reports, our findings show that post-reconsolidation recovery of conditioned responding is not a function of CS fear-relevance and that persistent reduction of fear, conditioned to fear-relevant CSs, can be achieved through behavioral manipulations of reconsolidation.